Analysis of Smoked Fish Processing and Income in Malalanda Village Kulisusu District North Button Regency Southeast Sulawesi Province - Sukmawati Abdullah; Surni Surni; Pertiwi Syarni; Rahayu Endah Purwanti; Normal Bivariant Padangaran; Waode Fatmawati (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2023)
This research aims to determine the process of processing tuna fish into smoked fish, which can produce a distinctive taste and aroma in Malalanda Village, Kulisusu District, North Buton Regency, and to determine the income obtained from the smoked fish processing business in fishing households in Malalanda Village, Kulisusu District, North Buton Regency and to determine the feasibility of the smoked fish processing business in Malalanda Village, Kulisusu District, North Buton Regency. This research was conducted in Malalanda Village, Kulisusu District, North Buton Regency. The research was conducted from December 2020 to August 2021. The sample in this study consisted of 11 respondents who work as smoked fish processors. Determination of the sample in this study was carried out using the census method. Namely, the entire population was sampled. The data analysis used is qualitative descriptive analysis, income analysis, and business feasibility. The research results show that processing tuna into smoked fish can produce a distinctive taste and aroma in Malalanda Village, Kulisusu District, North Buton Regency. Namely, in preliminary treatment, the fish to be smoked is sorted according to type, size, and freshness quality. It must be cleaned from dirt that can contaminate the product by washing with clean water and irrigating (removing the entrails and gills), clamping, drying, structuring, and smoking to preserve the fish and provide its color and distinctive smoky taste. Marketing. Income from the smoked fish processing business is IDR 2,487,209 per month. The R/C ratio value of 1.65 indicates that the smoked fish processing business is worthy of continuing development.